1 Thessalonians 4:4: Breaking the Impasse - SMITH, JAY E. (Bulletin for biblical research, 2001)
The crux interpretum τὸ ἑαυτοῦ σκεῦος κτᾶσθαι ἐν ἁγιασμῷ καὶ τιμῇ in 1 Thess 4:4 has traditionally been understood in one of three ways: (1) "acquire a wife for himself in holiness and honor" (NAB); (2) "live with your wife in a holy and honorable way" (TEV); and (3) "control your own body in holiness and honor" (NRSV). These three views are thoroughly evaluated, and new evidence, especially concerning the referent of σκεῦος as well as the semantic force of the present infinitive κτᾶσθαι, is brought to bear on the problem. This analysis suggests that by τὸ ἑαυτοῦ σκεῦος κτᾶσθαι ἐν ἁγιασμῷ καὶ τιμῇ Paul means that each one is to control his or her own body in holiness and honor or, perhaps more specifically, that each one is to control his or her sexual organ in holiness and honor.